حماية الحقوق المتبادلة بين أفراد الأسرة في الشريعة الإسلامية وقانون الأسرة الجزائري - سحارة, السعيد; ميدون, مفيدة (Revue jurisprudence; Vol. 11 No 01 (2019): مجلة الاجتهاد القضائي, 2019)
The aim of this study is to search in the protection of family rights in Islamic law and the Algerian family law; through the imposition of protection methods that concern members of the family, whether the husband or wife or children or parents, and try identify the rights of each of them whether these rights financial or moral and, whether they are limited to one or both spouses or shared between them, or were transitive to others in the family of children and parents. These rights were firmly established by Islamic law and confirmed by the texts of the Qur'an and the Sunnah, and urged must be execution, and has been enshrined by the Algerian legislator as is in the Islamic law and family law, and in certain provisions of other laws such as the constitution and criminal law, labor law; function law; and commercial law.